Caracterização das redes de suprimentos brasileiras de exportação de frango de corte: cenário atual e tendências futuras - Carona, Natércia Filipe Mendeiros (2008)
Globalization, technological, political and social breakthroughs create internal pressure inside the organizations which need to reply by developing its abilities and capacities. Business with focus on the international markets, must face bigger challenges. Even more complex and unstable environment, fluctuation import quotas and other barriers placed in the international commerce made quality stop being a competitive advantage in many industries and become a standard. The development of competitive strategies and supply chain networks are now crucial to survive in this environments. Brazil is one of the biggest world players in food production, specially beans and animal protein. Since 2004, Brazil is the second biggest chicken producer, and the first in exportation. The understanding of the characteristics underlying the supply network might help towards a more efficient orientation. Therefore, general objective of this study is to analyze the competitiveness in the Brazilian exportation agribusiness four poultry, by means of characterization of its supply networks. Moreover, it aims to identify which factors impact more in its success. For such purpose an analysis and synthesis of the relevant literature concerning Supply Networks Management and Agribusiness is developed, as well as the main tendencies and future challenges in the poultry business are researched. A framework resulting from the literature review was used in the multiple case study complying four companies from the exportation business of poultry. Results show that managing coordination, differentiation and reconfiguration, allows knowing the types of networks and verifying their skills to face future tendencies.